Kenya Gender and Poverty Assessment 2015-2016 : Reflecting on a Decade of Progress and the Road Ahead - World Bank (World Bank, Nairobi, 2019)
Following ten years of relatively robust economic growth, Kenya achieved lower-middle-income country status in 2014. The remarkable expansion of telecommunications and mobile financial services shifted Kenya’s economic paradigm to an extent rarely seen in developing countries. Poverty rates declined over the period but remain high by the standards of lower-middle-income countries. Due to the agricultural sector’s heavy dependence on rainfall, poverty reduction accelerated during years of good weather and slowed during years of drought. This report is divided into eight chapters. Chapter 1 provides an overview of the drivers of economic growth in Kenya, along with their fiscal implications. Chapter 2 describes Kenya’s progress in reducing monetary poverty between 2005-2016 and 2015-2016. Chapter 3 presents a synthesis of gender and poverty dynamics in Kenya. Chapter 4 analyzes rural livelihoods and explores various factors that may have contributed to or hindered the observed decline in rural poverty over the past decade. Chapter 5 examines the linkages between urbanization and poverty, with a focus on the challenges faced by the urban poor. Chapter 6 analyzes recent developments in Kenya’s education sector, along with their poverty and equity implications. Chapter 7 analyzes public health indicators and explores trends in health outcomes, service utilization, and health equity. Chapter 8 examines changes in the household vulnerability profile between 2005-2006 and 2015-2016.